Endoscopic balloon dilatation for pharyngo‐upper esophageal stricture after treatment of head and neck cancer. Issue 3 (24th September 2014) - Maejima, Ryuhei; Iijima, Katsunori; Koike, Tomoyuki; Ara, Nobuyuki; Uno, Kaname; Hatta, Waku; Ogawa, Takenori; Watanabe, Ken‐ichi; Katori, Yukio; Shimosegawa, Tooru
Abstract : Background and Aim: Dysphagia caused by pharyngo‐upper esophageal stricture is a complication of treatment for head and neck cancer. Endoscopic balloon dilation (EBD) is in widespread use as an effective and safe treatment for stricture in many areas of the gastrointestinal tract. In the present study, we investigated the efficacy and safety of EBD for pharyngo‐upper esophageal strictures that developed after treatment for head and neck cancer. Methods: From January 2010 to December 2013, the medical records and endoscopic findings of 19 consecutive patients with pharyngo‐upper esophageal strictures occurring after surgery and/or chemoradiotherapy for head and neck cancer were retrospectively examined. Results: Mean number of EBD sessions per patient was 6.6 (1–30), and mean maximum diameter of dilation was 15.8 (11–20) mm. Technical success was achieved in 16 of 19 (84.2%) patients, and only two major complications (bleeding and pha ryngeal edema) occurred in a total of 125 dilatation sessions (1.6%). Regarding the influence of chemoradiotherapy on the outcome of EBD, patients who had undergone chemoradiotherapy plus surgery experienced significantly more restenosis during the follow‐up period compared to those who had undergone surgery alone (50% vs 0%, P  < 0.05). Conclusions: This retrospective analysis demonstrated the efficacy and safety of exclusive EBD for pharyngo‐upper esophageal strictures occurring after treatment for head and neck cancer, indicating that the therapeutic application of EBD could be extended to such strictures. Patients who underwent chemoradiotherapy and surgery experienced more restenosis; hence, such patients should be carefully followed up after EBD treatment.